Estudo de influência de cobertura plástica na remoção de água de lodos de estações de tratamento de água em leitos de drenagem - Reis, Renan Felicio dos (2011)
Most of Water Treatment Plant (WTP) for public supply in Brazil use surface water as source and conventional complete cycle as treatment system. In this type of treatment wastewater are restrained/generated which vary mainly according to the type and amount of chemical added and the characteristics of the water resource. This wastewater is found mainly in clarifiers (sludge) and backwash water filter (BWF) from WTP. Unfortunately, most of Brazilian WTP launches its waste directly into water resources, violating Brazilian Law 9605 published in 1998. There are mechanical and natural technologies for water removal from wastewater restrained during the treatment. Once known that wastewater from WTP has fluid characteristic, some technologies to remove its water have been developed. A natural one is the drainage bed, developed and proposed by Cordeiro (2001). The drainage bed has basically two stages: drainage and evaporation. This dissertation presents results of a study, whose centre objective was to achieve improvements in water sludge removal restrained in clarifiers by the use of plastic cover (evaporation stage). Results of effective tests in prototypes located in Sao Carlos WTP (Sao Paulo State) with plastic cover have showed that this roof (commercial reference PVC 0.30 milimeters) uses has accelerated the evaporation process, and has protected sludge from rain. The height of the roof that presented the best result was 0.20 meters in relation to the board of prototype, realizing to obtain a sludge 56% dryer than in tests without the roof. Preliminary tests in laboratory scale generated a promising scenario for the use of cationic polymer in large scale doubling the efficiency of the initial drainage of sludge. However, other laboratory tests with different characteristics of geotextile blanket only confirmed the superiority of using woven blanket type with surface density of 600 g/m² (which had already been used in other studies), compared to the others, in reference to obtain better efficiency at the initial drainage of water present in raw sludge.